As questões de gênero na educação física escolar e a prática pedagógica de professores e professoras do município de Maracanaú-CE - Timóteo, Ítala Almeida (2019)
This paper aims to investigate and understand how gender issues have emerged during school Physical Education classes and to analyze how teachers of Physical Education in Maracanaú-CE have received such questions in their classes. For the constitution of the theoretical reference, the conception of gender as a social construct was established (GOELLNER, 2010; LOURO, 1997; MEYER, 2013; SCOTT, 1994), as well as the influence of the feminist movement on gender studies; conceptions of body and sexuality; gender marks in Brazilian Education; the debates on gender in Physical School Education; and the possibility of articulating gender issues in School Physical Education with a dialogical proposal based on Paulo Freire's studies. This research has a qualitative-descriptive disposition in order to understand how gender issues are approached in the teachers of Physical Education classes. The instruments used for data collection will be the diagnostic questionnaires, collectives interviews and systematized observations, and for the discussion of their results, thematic analysis was preferred as a path, discussing the categories, previously defined, a) contents; b) co-education; c) sexuality and gender identity; d) sexism and gender expectations; and also on categories arising from the field e) female participation in classes; f) the relationship between teachers and students; and g) the construction of dialogue on gender. As results of the research, it is announced that teachers show interest in discussing gender in their classes; that it influences their pedagogical practices; that through its interventions it is possible to mediate the conflicts. Teachers, throughout the observations, did not always approach the gender discussions in their classes, this proved to be a limiting situation, contributing to the reinforcement of generalized stereotypes. It was found that the teaching interventions and the dialogue are possible and favorable strategies in the search for gender equality in the Physical Education classes in the school.